The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1073/pnas.1216635109
|View full text |Cite
|
Sign up to set email alerts
|

Functional eukaryotic nuclear localization signals are widespread in terminal proteins of bacteriophages

Abstract: A number of prokaryotic proteins have been shown to contain nuclear localization signals (NLSs), although its biological role remains sometimes unclear. Terminal proteins (TPs) of bacteriophages prime DNA replication and become covalently linked to the genome ends. We predicted NLSs within the TPs of bacteriophages from diverse families and hosts and, indeed, the TPs of Φ29, Nf, PRD1, Bam35, and Cp-1, out of seven TPs tested, were found to localize to the nucleus when expressed in mammalian cells. Detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 55 publications
3
64
0
1
Order By: Relevance
“…Analysis of 29 TP led us to identify a bona fide nuclear localization signal within residues 1-37. Importantly, gene delivery into the eukaryotic nucleus was enhanced by the presence of 29 TP attached to the 5Ј-DNA ends (36). These findings show a common feature of TPs from diverse bacteriophages targeting the eukaryotic nucleus and suggest a possible common function by facilitating the horizontal transfer of genes between prokaryotes and eukaryotes.…”
Section: Structure-function Studies On the 29 Dna Polymerase And Termmentioning
confidence: 64%
“…Analysis of 29 TP led us to identify a bona fide nuclear localization signal within residues 1-37. Importantly, gene delivery into the eukaryotic nucleus was enhanced by the presence of 29 TP attached to the 5Ј-DNA ends (36). These findings show a common feature of TPs from diverse bacteriophages targeting the eukaryotic nucleus and suggest a possible common function by facilitating the horizontal transfer of genes between prokaryotes and eukaryotes.…”
Section: Structure-function Studies On the 29 Dna Polymerase And Termmentioning
confidence: 64%
“…Other prokaryotic proteins that are tightly bound to DNA molecules, like Agrobacterium VirD2, also have intrinsic NLSs required for DNA transfer to the eukaryotic nucleus (Rossi et al, 1993;Pelczar et al, 2004). Interestingly, we found that Φ29 TP also localizes in the eukaryotic nucleus when expressed in mammalian cells and, moreover, the presence of Φ29 TP at both ends of a linear DNA enhances gene delivery (Redrejo- Rodríguez et al, 2012). This nuclear targeting relies on the N-terminal residues 1-37 and, like cellular NLSs, its function requires energy, thereby suggesting that the phage TP contains an intrinsic bona fide NLS.…”
Section: Bacteriophage Tpsmentioning
confidence: 91%
“…Moreover, structure-function studies from other phage TPs beyond Φ29 or Φ29-like phages are not available, therefore their structural or functional domains are not easy to recognize. However, as expected from proteins that perform the same function, they share some structural features (Table 1), like a relatively small size and a high proportion of basic residues, some of them grouped in positively charged clusters in the N-terminal half of the protein (Redrejo- Rodríguez et al, 2012), which usually results in a high isoelectric point. Moreover, although the priming residue may be a serine, threonine or tyrosine, it is always in a loop between two α-helices and followed by an acidic residue (D/E), which has been recently shown to be involved in the stabilization of the priming loop/DNAP catalytic active site interaction (del Prado et al, 2013).…”
Section: Bacteriophage Tpsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is important to stress the fact that gene delivery into the eukaryotic nucleus was enhanced by the presence of ø29 TP attached at the 5' ends. 16 I would also like to mention some phage-host interactions in ø29 development. The early gen e56 encodes p56, a protein of 56 amino acids.…”
Section: Postdoctoral Trainingmentioning
confidence: 99%